PENGEMBANGAN E-LKPD BERBASIS PROBLEM SOLVING BERBANTUAN LIVEWORKSHEET UNTUK BERPIKIR KRITIS SISWA PADA MATERI TERMODINAMIKA - Linggar Jati, Putri; Emiliannur, Emiliannur; Winarno, Nanang (Jurnal MIPA dan Pembelajarannya, 2024)
The caliber of the instructional resources and learning styles employed has an impact on students' capacity for critical thought regarding the subject matter. The LKPD is one of the instructional resources that is frequently utilized in schools, according to the facts discovered in the field. Teaching resources that were formerly print-based have evolved into ones that can be accessible through the E-LKPD thanks to technological advancements. The Problem-Solving model is one of the learning strategies that can assist students in developing their critical thinking abilities. The development of E-LKPD Based on Problem Solving is one of the implemented solutions. This study aims to ascertain whether a legitimate and useful E-LKPD is feasible. Using the ADDIE development approach, the research was done as a sort of research and development (R&D) study. Five experts collected the data source from the validation findings. Twenty-five SMA grade XI students and two teachers provided the practicality data source. V Aiken was the data analysis approach utilized for instrument and product validity, whereas percentage techniques were used for product practicality. the validity test's 0.90 results in a valid category. The practicality test results from the teacher were 89% in the highly practical category, while the test results from the students were 98% in the same area. Thus, it can be said that the E-LKPD Based on Problem Solving design is legitimate and useful.